Intercellular adhesion molecule-1 and MHC antigens on human intrahepatic bile duct cells: effect of pro-inflammatory cytokines. Issue 9 (September 1993) - Ayres, R C; Neuberger, J M; Shaw, J; Joplin, R; Adams, D H
Abstract : Human intrahepatic biliary epithelial cells were isolated from the livers of patients with primary biliary cirrhosis and from normal livers and established in primary culture. The in vitro expression of intercellular adhesion molecule-1, HLA class I, and HLA class II on biliary epithelial cells was studied in response to tumour necrosis factor-alpha (0-500 U/ml), interferon-gamma (0-500 U/ml), and interleukin-1 (0-5 U/ml) by immunohistochemical staining and a semiquantitative scoring system validated by spectrophotometry and previously validated by laser confocal microscopy. The non-stimulated expression of intercellular adhesion molecule-1 and HLA class II was higher on cells derived from the primary biliary cirrhosis liver than on cells from normal liver, a difference not seen with HLA class I expression. A statistically significant increase in intercellular adhesion molecule-1 expression was seen with all three cytokines in cells derived from both primary biliary cirrhosis and normal liver. Increase in HLA class I expression was seen only with interleukin-1 5 U/ml for cells derived from both normal and diseased liver. Increase in HLA class II expression was seen only with interferon-gamma 500 U/ml for cells derived from diseased liver and with interleukin-1 5 U/ml for cells derived from both diseased and normal liver. These data show that pro-inflammatory cytokines increase expression of intercellular adhesion molecule-1, HLA class I, and HLA class II on human intrahepatic biliary epithelial cells in vitro and are consistent with the hypothesis that these locally acting factors may play a part in the pathogenesis of immune mediated disorders such as primary biliary cirrhosis in which immune mediated bile duct damage occurs.